PERBEDAAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DENGAN THINK PAIR SHARE SISWA KELAS VIII SMP NEGERI 28 MERANGIN - Wasiatun Naammah (Mat-Edukasia, 2018)
This study aims to describe the learning outcomes of mathematics using the Jigsaw type cooperative learning model better than Think Pair Share on Merangin 28th Junior High School students' building material. This study uses a quantitative approach to the experimental method with a population of eighth grade students totaling 36 people. The sampling technique uses Simple Random Sampling. The selected sample is class VIII B as the experimental class 1 and VIII A as the experimental class 2. The technique of collecting data is through a test of mathematics learning outcomes in the form of essay questions with a number of four items in the matter of building space. The data analysis technique used to test hypotheses is the u-test. From the analysis of the final test data in the experimental class 1 obtained an average score of 71.53, variance of 805.41, while the experimental class 2 obtained an average score of 66.36, variance of 697.786. -U test results obtained, sig at significance level of 0.05 is 0,217 turns sig> or 0.217> 0.05, H0 accepted. The conclusion of this study is that the mathematics learning outcomes using the Jigsaw type cooperative learning model are no better than Think Pair Share in the room building material of Class VIII students of SMP N 28 Merangin. Keywords: Mathematics Learning Outcomes, Jigsaw Cooperative Learning Model with Think Pair Share.